2003
DOI: 10.1086/379543
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Presence of a Single or Binary Black Hole in the Globular Cluster NGC 6752 with Pulsar Dynamics

Abstract: The five millisecond pulsars that inhabit NGC 6752 display locations or accelerations that are quite unusual compared to all other known pulsars in globular clusters. In particular, PSR A, a binary pulsar, lives in the cluster halo, while PSR B and PSR E, located in the core, show remarkably high negative spin derivatives. This suggests that some uncommon dynamical process is at play in the cluster core, which we attribute to the presence of a massive perturber. Here we investigate whether a single intermediat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 42 publications
6
73
0
Order By: Relevance
“…Such systems suggest the presence of a massive object in the center of the cluster. Colpi et al (2002Colpi et al ( , 2003 show that the off-center location of the pulsars can be explained with scattering from a binary of stellar mass black holes or a single intermediatemass black hole. This supports the idea that high-velocity stars in globular clusters may be produced by single or binary black holes.…”
Section: Comparison With Other Globular Clustersmentioning
confidence: 99%
“…Such systems suggest the presence of a massive object in the center of the cluster. Colpi et al (2002Colpi et al ( , 2003 show that the off-center location of the pulsars can be explained with scattering from a binary of stellar mass black holes or a single intermediatemass black hole. This supports the idea that high-velocity stars in globular clusters may be produced by single or binary black holes.…”
Section: Comparison With Other Globular Clustersmentioning
confidence: 99%
“…That offset is larger than for any other GC pulsar except NGC 6752A (Corongiu et al 2006), where exotic ejection mechanisms have been invoked to explain its position (e.g. Colpi et al 2003). .…”
Section: Ensembles Of Pulsarsmentioning
confidence: 76%
“…Based on radio emission as a possible test of the existence of IMBHs in GCs, Maccarone (2004) suggested that the radio, rather than the X-ray, observations can be a more successful test for a central IMBH and have calculated expected radio flux densities for a few possible candidates. One more technique to search for the massive BH-BH binary system in the core of GCs is the use of exotic ejected binary systems, for which the cluster NGC 6752 is a very good candidate, having a binary pulsar system at 3.3 half-mass radii from the core and a high central mass-to-light ratio (Colpi et al 2003). In Table 6, the last but one column lists the reason for the selection of a cluster.…”
Section: Black Hole Mass Estimates In a Sample Of Globular Clustersmentioning
confidence: 99%
“…"=possible p.c.c. (Trager et al 1995;Lugger et al 1995); "HVS"=high velocity stars ; "radio"=radio observations (Maccarone 2004;Bash et al 2008); "EHB"=extreme horizontal branch stars (Miocchi 2007); "PSR"=detection by pulsar dynamics (Colpi et al 2003); "B. "=Baumgardt's sample (Baumgardt et al 2005).…”
mentioning
confidence: 99%